Tarik-Ulur Antara Radikalisme dan Multikulturalisme dalam Studi Agama di Abad Ke 21 - Putra, Andi Eka (Universitas Islam Negeri Raden Intan Lampung, 2019)
The rise of Islam mentioned by some observers of Islamic studies (Islamic studies) in the country often brings its own anomalies. The awakening often brings effects and effects that are often not expected. For example, the strengthening of notions that have not been so deeply rooted in the country, such as the understanding of terrorism and radicalism. Elsewhere, intellectuals and reviewers of the relationship of religions offer other forms such as multiculturalism. These are the two most striking faces of the Milineal or 21st century religious model: the face of radical diversity and the face of multicultural diversity. The first requires a single interpretation, the second puts forward a pluralist interpretation. If the radical face looks fierce, hard, then the multicultural face is more polite and open. Both typologies are theoretically and practically very fluid, and not as strict as the binary opposition between black and white. But both of them are quite representative of the latest variants of religion that can be found in a variety of political discourses, scientific discussions, writings in the form of news and articles in the news, Tolkshow, and serasehan. Both models are even included in the study of religious studies are almost as popular as the terms